A new MRI severity score to predict long-term adverse neurologic outcomes in children with congenital Cytomegalovirus infection. (19th March 2021) - Lucignani, Giulia; Rossi Espagnet, Maria Camilla; Napolitano, Antonio; Figà Talamanca, Lorenzo; Calò Carducci, Francesca Ippolita; Auriti, Cinzia; Longo, Daniela
Abstract: Background: Congenital cytomegalovirus (CMV) infection is one of the main causes of deafness in childhood. It frequently causes serious long-term neurological sequelae. In children who are asymptomatic at birth, tests to accurately predict these sequelae are still unavailable. Aims: We describe different brain MRI patterns of congenital CMV infection correlated with clinical data and propose a new MRI severity score to early predict long-term neurological sequelae. Materials and methods: We explored clinical records and neuroimaging data of 224 neonates and children with congenital Cytomegalovirus infection, 180 of them did not meet inclusion criteria. Forty-four babies met inclusion criteria and were enrolled in the study. We retrospectively collected clinical data concerning hospitalization, 2 years outpatient follow-up and brain MRI findings of those 44 children, symptomatic and asymptomatic at birth. Clinical data were then correlated with children's brain MRI examinations. We defined neurological and sensorial impairment (hearing or visual) as "adverse neurological outcomes". Brain MRI score was constructed assigning different values to white matter and ventricular dilation. Results: In 44 children enrolled in the study we found that 28/35 (80%) with abnormal and 2/9 (22, 2%) with normal MRI examination developed adverse neurological outcomes (OR = 3.6) (95% IC 1.0–12.0). Infants who were symptomatic at birth showed a probability of MRI brain lesions 3.2 times higher than those who were asymptomatic. Ten out of 17 (59%) children who were asymptomatic at birth showed MRI-WM alterations or ventriculomegaly. Conclusions: Brain MRI abnormalities, such as WM alterations and ventriculomegaly, expressed as MRI score higher than 2 are associated with an increased probability of long-term adverse neurological outcome in congenitally CMV infected infants, symptomatic and asymptomatic at birth.